Eating breakfast and avoiding the evening snack sustains lipid oxidation - Kevin Parsons Kelly; Mcguinness, Owen P; Buchowski, Maciej; Hughey, Jacob P; Chen, Heidi; Powers, James; Page, Terry; Johnson, Carl Hirschie (bioRxiv, 2020)
Circadian (daily) regulation of metabolic pathways implies that food may be metabolized differentially over the daily cycle. To test that hypothesis, we monitored the metabolism of older subjects in a whole-room respiratory chamber over two separate 56-h sessions in a random crossover design. In one session, one of the three daily meals was presented as breakfast whereas in the other session, a nutritionally equivalent meal was presented as a late-evening snack. The duration of the overnight fast was the same for both sessions. Whereas the two sessions did not differ in overall energy expenditure, the respiratory exchange ratio (RER) was different during sleep between the two sessions. Unexpectedly, this difference in RER due to daily meal timing was not due to daily differences in physical activity, sleep disruption, or core body temperature. Rather, we found that the daily timing of nutrient availability coupled with daily/circadian control of metabolism drives a switch in substrate preference such that the late-evening snack session resulted in significantly lower lipid oxidation compared to the breakfast session. Therefore, the timing of meals during the day/night cycle affects how ingested food is oxidized or stored in humans with important implications for optimal eating habits.